Eksistensi Teknologi Informasi dan Komunikasidalam Proses Pembelajaran di Era Society 5.0 - Suharnadi, Putra; F, Firman; Sukma, Dina; Kurniawati, Elvia (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the existence of information and communication technology in the learning process in Indonesia in facing the Society 5.0 era. This research method is qualitative with a literature study approach. The data collection technique in this study is to use literature studies where literature studies are activities to collect materials related to research. The sources of information can come from books, and also scientific journals. These data are used as a basis for strengthening arguments related to the transformation of education in Indonesia towards a more modern and adaptive education system to technological developments. The results of the study show that the existence of information and communication technology in the learning process in the Society 5.0 era requires the integration of digital technology, the development of digital competencies of teachers and students, and the transformation of more interactive and personal learning methods.